The Online Assessment Tools of the MenPas 1.0 Platform, a Reliable and Sustainable Alternative for Psychosocial Research: A Literature Review - Pérez-Romero, Nuria; Morales-Sánchez, Verónica Odilia; Pastrana-Brincones, José Luis; Sánchez-García, Carolina; Hernández-Mendo, Antonio; Reigal-Garrido, Rafael Enrique (MDPI, 2023)
New technologies have improved the efficiency and sustainability of psychosocial research. However, online assessment tools may differ from traditional paper-based ones in different domains. This study aims to provide an updated perspective of the online assessment advantages of a psychosocial platform called MenPas 1.0. A literature review was conducted, choosing validated questionnaire studies located in the MenPas 1.0 platform, specifically, motivation and hypnosis questionnaires. A total of five studies showing the psychometric properties of psychosocial evaluation tools were analysed and compared with their previous paper-based studies. In addition, internet impact over the last 20 years was analysed according to gender, age, nationality, and employment status. Finally, a conclusion was drawn on the impact of these tools on sustainability. The results showed that online studies have a higher number of participants (5866 users in 5 studies versus 5623 participants in 11 studies) and higher reliability rates than those of previous paper-based ones. A decrease in the social gap over the years was also found and the contribution of online tools to sustainability was discussed. This study could show the importance of the analysis of psychometric properties in online tools, the need for further research, and encourage their use in psychosocial assessment.
Keywords: Psicología - Investigación; Motivación (Psicología); Hipnotismo; Desigualdad social; Assessment; Motivation; Sustainability; Hypnosis; Social gap